Flexibility Working Space di Lingkungan Direktorat Jenderal Bea dan Cukai: Dampak bagi Kinerja Organisasi - Husnia, Rifqi Yulan; Nasution, Vivi Indra Amelia (Spirit Publik: Jurnal Administrasi Publik, 2023)
Flexible Working Space (FWS) is an alternative to new working patterns that began to be widely applied since the Covid 19 Pandemic. FWS is implemented by private agencies and the government, such as the Directorate General of Customs and Excise (DJBC) of the Ministry of Finance. Therefore, this study intends to explain how implementing Workplace Flexibility impacts the performance achievements of the Directorate General of Customs and Excise (DJBC). This research will juxtapose data from DGCE performance reports from 2018 to 2022. Interviews, literature studies, and other official documents support this research. The collected data were analyzed using a qualitative descriptive method. The result is that implementing flexible working space has led DJBC to achieve an Excellent Predicat of Organizational Performance Value. Either performance indicator with a significant role is the realization of state revenue in customs and excise. This is proven by realizing achievements that continue to increase yearly. Thus, it shows that organizational performance does not have a negative impact due to the implementation of Flexible Working Space at DJBC.